2014
DOI: 10.1038/nature13479
|View full text |Cite
|
Sign up to set email alerts
|

Pro-resolving lipid mediators are leads for resolution physiology

Abstract: Preface Advances on mechanisms in resolution of acute inflammation uncovered a new genus of pro-resolving lipid mediators that include separate families of molecules: lipoxins, resolvins, protectins and maresins, collectively coined specialized pro-resolving mediators (SPM). Synthetic SPM possess potent bioactions when administered in vivo. In animal experiments, SPM evoke anti-inflammatory and novel pro-resolving mechanisms as well as enhance microbial clearance. While identified in inflammation-resolution, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

37
2,972
4
17

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 2,428 publications
(3,030 citation statements)
references
References 120 publications
(246 reference statements)
37
2,972
4
17
Order By: Relevance
“…EPA and DHA are also converted to specialized proresolving lipid mediators, with EPA and DHA being the respective precursors of the E‐series and D‐series resolvins 32. The resolvins have been shown to stimulate the resolution of acute inflammation by stopping further neutrophil recruitment to inflamed tissues and stimulating nonphlogistic infiltration of monocytes, which differentiate into resolution macrophages 33. These resolution macrophages then phagocytize and clear apoptotic neutrophils and debris, a process termed efferocytosis, which is a key step in resolution and prevention of chronic inflammation 33, 34.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EPA and DHA are also converted to specialized proresolving lipid mediators, with EPA and DHA being the respective precursors of the E‐series and D‐series resolvins 32. The resolvins have been shown to stimulate the resolution of acute inflammation by stopping further neutrophil recruitment to inflamed tissues and stimulating nonphlogistic infiltration of monocytes, which differentiate into resolution macrophages 33. These resolution macrophages then phagocytize and clear apoptotic neutrophils and debris, a process termed efferocytosis, which is a key step in resolution and prevention of chronic inflammation 33, 34.…”
Section: Discussionmentioning
confidence: 99%
“…The resolvins have been shown to stimulate the resolution of acute inflammation by stopping further neutrophil recruitment to inflamed tissues and stimulating nonphlogistic infiltration of monocytes, which differentiate into resolution macrophages 33. These resolution macrophages then phagocytize and clear apoptotic neutrophils and debris, a process termed efferocytosis, which is a key step in resolution and prevention of chronic inflammation 33, 34. Recent research has shown that omega‐3 fatty acids may hasten the resolution of inflammation when converted to resolvins 32, 33.…”
Section: Discussionmentioning
confidence: 99%
“…Efficient resolution of inflammation is an active process required to clear pathogens, avoid tissue damage, and restore function. 1,2 Unabated inflammation is an underlying cause of many chronic diseases. 3 Self-resolving inflammation is divided into an early-onset phase and a resolution phase.…”
Section: Inflammation and Its Natural Resolution Are Host-protectivementioning
confidence: 99%
“…In stress, protein synthesis is increased but less than protein degradation. The substrates we are administrating may be harmful at the onset of ischemia reperfusion, inhibiting autophagy [13], but could also be helpful in limiting the critical decrease of cell ATP [14], preventing programmed cell death or resolving inflammatory processes, for example, n-3 fatty acids producing lipoxin and resolvin [15]. While nutrition may never be the magic bullet to cure critical illness, improved understanding and its skilled use may improve cell metabolism, thus allowing the organism to better cope with injury.…”
mentioning
confidence: 99%